EKOSISTEM BISNIS PEMBESARAN IKAN BANDENG (CHANOS CHANOS) DI DESA GRINTING, KECAMATAN BULAKAMBA, KABUPATEN BREBES - Wahyu, Taufik; Firdaus Alatas, Nahl; Johanda Putra, Joni; Budhi Pramono, Taufik (Program Studi Budidaya Perairan Universitas Mataram, 2022)
Milkfish (Chanos chanos) is a leading fish commodity in Brebes Regency. The sustainable development of milkfish requires a supportive business ecosystem. The purpose of this study was to determine the business ecosystem of milkfish enlargement business in Grinting Village, Bulakamba District, Brebes Regency. Research data collection was carried out in March-April 2022 in Grinting Village, Bulakamba District, Brebes Regency. This research method uses an active survey with purposive sampling. Business ecosystem data is obtained directly through interviews with groups of fish farmers using a questionnaire. The results of the business process analysis show that the supply of milkfish nener in Grinting village comes from Bali. There is 1 member of the group who specializes in nursing efforts to ensure the supply of nener for rearing. The cultivation process generally applies the traditional system which is carried out for 4-6 months. The production output is milkfish consumption with the size of 6-7 fish/Kg and 1-2 fish/Kg. The market or customer for milkfish consumption is still within the scope of the Central Java region. Milkfish cultivators have built a business ecosystem through the application of SIPOC in a close system in a sustainable aquaculture business.